1992
DOI: 10.1172/jci116065
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationships of interleukin-3. An analysis based on the function and binding characteristics of a series of interspecies chimera of gibbon and murine interleukin-3.

Abstract: IL-3 is a glycoprotein cytokine involved in the hematopoietic response to infectious, immunologic, and inflammatory stimuli. In addition, clinical administration of recombinant IL-3 augments recovery in states of natural and treatment-related marrow failure. IL-3 acts by binding to high affinity cell surface receptors present on hematopoietic cells. To determine the site(s) at which IL-3 binds to its receptor, we analyzed a series of interspecies chimera of the growth factor for species-specific receptor bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 55 publications
(30 reference statements)
1
11
0
2
Order By: Relevance
“…Structure-function studies using site-directed mutagenesis have revealed that residues 21, 22, 27, 33, 43, 44, 48, 53, 58, 61, 64, 94, 101, 110, 111, 115, and 116 are important for activity (9 -13), although several of these residues may be buried in the IL-3 structure. In addition, mouse-gibbon chimeras (14) and site-directed mutagenesis (15) of IL-3 identified two noncontiguous regions near the N and C termini that are required for biological activity.…”
Section: Human Interleukin (Il)mentioning
confidence: 99%
“…Structure-function studies using site-directed mutagenesis have revealed that residues 21, 22, 27, 33, 43, 44, 48, 53, 58, 61, 64, 94, 101, 110, 111, 115, and 116 are important for activity (9 -13), although several of these residues may be buried in the IL-3 structure. In addition, mouse-gibbon chimeras (14) and site-directed mutagenesis (15) of IL-3 identified two noncontiguous regions near the N and C termini that are required for biological activity.…”
Section: Human Interleukin (Il)mentioning
confidence: 99%
“…Under typical conditions, 5 × 10 4 CD34-enriched marrow cells were suspended per milliliter of virus supernatant supplemented with 4 g/ml protamine sulfate (Sigma), 50 ng/ml recombinant human SCF (a gift from Amgen, Thousand Oaks, CA, USA), 100 ng/ml recombinant human IL-6 (a gift from Sandoz Pharmaceuticals, Hanover, NJ, USA), and 5% v/v conditioned medium from BHKIL-3 cells (a gift from K Kaushansky, University of Washington, Seattle, WA, USA) 51 containing gibbon IL-3. Cultures were incubated in tissue culture-treated multiwell dishes at 33°C, 5% CO 2 .…”
Section: Transduction Conditionsmentioning
confidence: 99%
“…This study identified several discrete regions of hIL-3 that are important for activity. To date, the relationships of these discontinuous regions to one another could only be inferred on the basis of secondary structure prediction and homology modeling of hIL-3 (3,12,17,19). The recently available three-dimensional structure of an hIL-3 variant (7) provides for the first time an experimentally derived model to understand the effect of these mutations.…”
Section: Interleukin-3 (Il-3)mentioning
confidence: 99%
“…Following the formation of the high affinity IL-3⅐IL-3R complex, signal transduction is mediated by the ␤ chain. Although the precise stoichiometry of the IL-3 receptor has not been established, we refer to the receptor as a heterodimer for simplicity.Several approaches have been undertaken to define the regions of hIL-3 that interact with the receptor, including constructing interspecies chimeras (12, 13), mapping neutralizing and non-neutralizing anti-IL-3 monoclonal antibody epitopes (12,14), and site-specific mutagenesis (14 -20). These studies identified sequences important for activity in both N-and Cterminal regions of IL-3 and revealed many specific sites where amino acid substitutions lead to significant changes in receptor binding affinity and growth-promoting activity.…”
mentioning
confidence: 99%